Ketepatan takwim Hijri Malaysia berdasarkan cerapan fasa bulan purnama - Baharrudin, Zainal; Akmal Aishah, Rahimi (2019)
The beginning of the month for the Hijri calendar begins when the Moon appears or uses the method of hisab. In context Hijri calendar in Malaysia, determination for the crescent moon by the imkannur rukyah. According to this method, the beginning of the Hijri month begins when the Moon exists and visible. Based on this justification the date of the new Hijri month was arranged. One of the main features of the Islamic calendar, including the Hijri calendar, is that the calendar period must same with the Moon phase. Therefore, the accuracy of the sighting crescent moon criterion can be tested by the Moon phase. For this purpose, the test can be done by comparing the phases of the Moon with the Hijri calendar. By observation the phases of the Moon phases on the dates near the full moon, on the 12th, 13th, 14th, 15th and 16th nights, the accuracy of the Moon phase with the Hijri date is analyzed. The analysis was performed by comparing the sunset with the rising Moon, as well as the percentage of phases of the Moon captured in photography. This information matches the Hijri calendar to find out the accuracy of the Moon phase with the Hijri calendar. The results show that, based on the date of the Malaysia Hijri calendar, the full moon phase occurs partly on the 14th night of the 15th day and the rest on the 15th night of the 16th day.